Polri dan UU Anti Teror Baru - Muradi Muradi (Sekolah Tinggi Ilmu Kepolisian, 2017)
The trends that evolved in the prevention and counter terrorism in the last twenty years in the world and including Indonesia positioned the State must be observant in responding to the threat of terrorism. This is an integral part of the growing dynamics of terrorism threats. Choosing whether the threat of terrorism is considered a threat to the sovereignty of the State or the threat of extraordinary crime must be responded in a more specific form, including adjustments to the use of existing laws. The existence of the new Anti-Terror Law makes the Police a main component in the prevention and counter terrorism must also make adjustments in order to remain effective in carrying out its roles and functions. However, this paper argues that the prevention and counter of terrorism by the police can be done by integrating the readiness of human resources as well as changes in the pattern of handling more integrated. Therefore, this paper will also analyze the extent to which the model of prevention and combating terrorism by the Police can be effective in positioning the institution with the new Anti-Terror Law, with a more balanced scheme of role and function between prevention and combating in terrorism.